Should we change the stroke length for jordanian swimmers? - Kilani, H.; Statieh, S. (ISBS - Conference Proceedings Archive (Konstanz), 2006)
In order to investigate the stroke length effect on the final swimming time, an adaptation of stroke frequency was assigned, and a change of stroke length was observed in the National Youth Jordanian swimming team. Therefore, the purpose of this study was to identify the effect of the relation between stroke length and stroke rate on the final time, for 25m crawl swimmers, and to determine the kinematics variables that are related to the free swimming phase. These variables were stroke length SL, stroke rate SR, velocity V, efficiency factor EF and final time FT. Subjects were assigned to swim at their maximum speed with certain length of strokes three times during the experiment so three groups were classified: Normal Stroke NS, Long Stroke LS and Short Stroke SS. The NS was the optimum although it may increase the EF if they adopt longer SL and adapt their techniques for the new changes in the training sessions.